Visual Style of 21 Intelectual Property Right (IPR) Certified Lasem Batik Motifs as the Expression of Cultural Hybridity - Setyoningrum, Yunita; Lukman, Christine Claudia; Rismantojo, Sandy (Bina Nusantara University, 2019)
The problem in this research derived from the fact that many Lasem batik entrepreneurs nowadays had limited knowledge of the novel characteristics of Lasem batik and hardly aware of its geographical indication. The research objective was to identify how the cultural hybridity of Chinese-Javanese culture and Lasem geographical environment were reflected by both the Tionghoa Peranakan-descent and Javanese-descent artists through the visual signs in the batik design. The purposive samples used were 21 Lasem batik motifs made by Tionghoa Peranakan-descent and Javanese-descent entrepreneurs which already IPR-certified. The method used was a compositional interpretation by interpreting each batik motif composition according to its content (subject matter), color, spatial organization, and expressive content (the combined effect of subject matter and visual form). The finding reveals that Lasem visual style hybridity is generally visible in: (1) the use of Chinese subject matter combined with Javanese motifs, (2) the use of Chinese subject matter combined with local Javanese isen-isen (texture), and (3) the rich use of red (from Chinese batik visual style) combined with brown (from Javanese batik visual style). This finding can be used as a reference guide for latter Lasem batik entrepreneurs to maintain the particular characteristics of Lasem batik while developing other batik motifs innovation.